1998
DOI: 10.1111/j.1528-1157.1998.tb01288.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Utilization During Interictal Intervals in an Epilepsy Model Induced by Pilocarpine: A Qualitative Study

Abstract: Summary:Purpose: Interictal intervals in pilocarpineinduced chronic epilepsy are characterized by apparent normal electrographic activity and longer sleep periods or drowsiness or both. Sparse information exists concerning the neural network activity during these seizure-free intervals. In our research, a [ ''C]2-deoxy-~-glucose (2DG) autoradiographic technique was used to investigate interictal changes in the metabolism of the epileptic rat brain.Methods: Epileptic rats were monitored by video-EEG for -120 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 17 publications
3
15
1
Order By: Relevance
“…Supporting our finding, Dal-Pizzol et al [4] found a decrease in TBARs levels in the hippocampus in the pilocarpine model during SRS and explained it by the neuronal loss [10,46] and hypometabolism observed in this structure [47]. Curcumin treatment resulted in a significant decrease in LP below control and pilocarpine-treated levels.…”
Section: Discussionsupporting
confidence: 83%
“…Supporting our finding, Dal-Pizzol et al [4] found a decrease in TBARs levels in the hippocampus in the pilocarpine model during SRS and explained it by the neuronal loss [10,46] and hypometabolism observed in this structure [47]. Curcumin treatment resulted in a significant decrease in LP below control and pilocarpine-treated levels.…”
Section: Discussionsupporting
confidence: 83%
“…The increased metabolic rate in LP during the interictal period may be a result of the activation of cerebral circuits controlling SRSs initiation and/or generalization 6 . The chronic epileptic conditions may be associated with increased inhibitory influences during the interictal state, which could reflect reactive homeostatic mechanisms to prevent seizure initiation or restrict ictal propagation once epileptogenesis occurs 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these differences may be particularly important for understanding the triggering and spreading mechanisms underlying epileptic activity during status epilepticus and recurrent seizures 6 . Our results reinforce those considerations since we showed that LP lesion by ibotenic acid in chronic rats results in an increase of seizures frequency.…”
Section: Discussionmentioning
confidence: 99%
“…The anatomic substrates activated during seizure activity differ from those activated during interictal intervals 23 . We have recently showed that increased metabolic rate in the lateral posterior thalamic nuclei during the interictal period may be a result of the activation of cerebral circuits controlling SRSs initiation and/or generalisation.…”
Section: Discussionmentioning
confidence: 99%